EDUKASI DEVELOPMENTAL CARE MENINGKATKAN PENGETAHUAN, MOTIVASI DAN KEPUASAN PERAWAT DALAM MERAWAT - Ernawati, Ernawati (Jurnal Kesehatan Holistic, 2017)
Developmental care is one of the important components in the nursing care of Low Birth Weight (LBW), which aims to prevent stress on LBW so that it can support development of neonate. This study aimed to identify the influence of education developmental care for knowledge, motivation and satisfaction of nurses in the care of LBW. This research design using quasi-experimental pretest-posttest design without control, with 20 pediatric nurse respondents in Husada Hospital Jakarta. The results showed there was a significant increase in the level of knowledge and motivation of nurses (p value = 0.000), where as the level of nurses’s satisfaction showed no significant results (p value = 0.083). Educational Developmental care is effective in improving knowledge and motivation of nurses. Researchers recommend that is importance giving education of developmental care to pediatric nurses, because it will affect the knowledge and motivation of nurses in caring for LBW